The phenomenon of violence and Students’ Violations in University Life at Al-Quds University from Students’ perspectives - Hamarsheh, Abdelsalam Mohammad (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the violence phenomenon and student violations in university life at Al-Quds University from the students’ point of view. The researcher used the descriptive-analytical method, and the study sample consisted of (481) male and female students, who were randomly selected. The main results indicated that there were no statistically significant differences in the forms and manifestations of violence in university life at Al-Quds University, while it was found that there are statistically significant differences due to the variable of the academic level. The results also indicated that there were no statistically significant differences in the students’ attitudes towards violent behavior and student violations in university life at Al-Quds University from the students’ point of view. Moreover, it was found that there are statistically significant differences in students’ attitudes towards violent behavior and student violations in university life at Al-Quds University attributed to the GPA variable, and the differences were in favor of 60-75%. Furthermore, the results of the study showed that there were no statistically significant differences in the field of students’ suggestions to reduce violence and student violations in university life at Al-Quds University from the students’ point of view attributed to gender sex variable, place of residence, GPA, academic level and college.